7th International Conference on Imaging for Crime Detection and Prevention (ICDP 2016) 2016
DOI: 10.1049/ic.2016.0079
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of smuggled high-risk security threats using Deep Learning

Abstract: The security infrastructure is ill-equipped to detect and deter the smuggling of non-explosive devices that enable terror attacks such as those recently perpetrated in western Europe. The detection of so-called "small metallic threats" (SMTs) in cargo containers currently relies on statistical risk analysis, intelligence reports, and visual inspection of X-ray images by security officers. The latter is very slow and unreliable due to the difficulty of the task: objects potentially spanning less than 50 pixels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
(40 reference statements)
0
21
0
Order By: Relevance
“…In our previous work on cargo, we showed that using a trained-from-scratch Convolutional Neural Network (CNN), we could detect 90% of SMTs synthetically concealed in stream-of-commerce images of ISO containers, whilst raising 6% false alarms. 7 In addition, we found that by feeding the CNN the log-image as an additional input channel, the detection performance of the network was improved considerably.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In our previous work on cargo, we showed that using a trained-from-scratch Convolutional Neural Network (CNN), we could detect 90% of SMTs synthetically concealed in stream-of-commerce images of ISO containers, whilst raising 6% false alarms. 7 In addition, we found that by feeding the CNN the log-image as an additional input channel, the detection performance of the network was improved considerably.…”
Section: Introductionmentioning
confidence: 92%
“…[6][7][8][9][10][11] Of these, cargo offers the most challenge for Automated Threat Detection (ATD). Images are typically much larger, and threats easier to conceal amongst dense or complex cargo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of CNNs on X-ray images for baggage inspection has been limited to the direct application of basic 2D detection algorithms, either with pretraining on photographic images or training from scratch. Jaccard et al [16] propose a black-box approach to multi-view detection by extracting CNN features from all views, concatenating them, and feeding them to fully-connected layers. Yet, the accuracy fell short of that of the original single-view detection.…”
Section: Related Workmentioning
confidence: 99%
“…[1][2][3] The Convolutional Neural Networks (CNNs) which were used obtained accuracy by training on 10 5 labelled images generated through Threat Image Projection (TIP) onto a stream-of-commerce (SoC) dataset. It is easy to conceive of scenarios where, even with TIP, training data is limited in quantity and scope-for example when a new generation of scanner is introduced, or a new threat emerges-while producing additional training data would be costly and time consuming.…”
Section: Introductionmentioning
confidence: 99%